Composite selection signal analysis: Uncovering candidate genes and quantitative trait loci in Indian sheep breeds - Sapna Nath; Satish Kumar Illa; Destaw Worku; Sabyasachi Mukherjee; Anupama Mukherjee; Vinod Kumar Yata (PLoS ONE, 2026)
Selective pressures, both natural and artificial, have significantly influenced the genomic architecture of domesticated sheep. Understanding their underlying molecular mechanisms is critical for developing efficient breeding programs to conserve and improve economically important traits in native breeds. In this study, we analysed high-density 50K SNP data from three Indigenous sheep breeds: Chanthangi (CHA, n = 29), Garole (GAR, n = 24), and Deccani (IDC, n = 26), each native to diverse climatic regions of India. We implemented a novel SNP-based de-correlated composite of multiple signals (DCMS) statistic, which integrates p- values from five selection metrics viz., FST, H1, H12, Tajima’s D, and nucleotide diversity (π) into a unified measure. The SNP-based DCMS approach offers finer resolution and complements window-based methods by enabling more precise localisation of selection signals and candidate genes. Multiple testing correction was applied at a False Discovery Rate (FDR) threshold of <5% to detect significant genomic regions . Comprehensive gene and quantitative trait loci (QTL) annotation and enrichment analysis of these regions were also performed for each breed. The DCMS analysis identified 21, 10, and 14 novel and breed-specific putative genes in the Chanthangi, Garole, and Deccani breeds, respectively, as well as 10, 28, and 13breed-specific QTL regions. The identified genes and QTLs are associated with diverse phenotypic traits, including growth and muscle development ( CNTNAP5, DOCK3 ), reproduction ( TCERG1L, BUB1, UNC5C, C2CD5, BBX ), wool trait ( TPPP3, P2RY6 , FGF10, POU2F1 , FAM168A ), disease resistance ( MTSS1, B4GALNT3 ), environment adaptation ( TRMT12, MAPKAPK3 ), domestication ( LRRC36 ). The QTLs identified are associated with body conformation (body measurements and bone area), production (milk fat yield), reproduction (total lambs born), disease resistance (hemonchus resistance, foot rot, and pneumonia susceptibility), and health (platelet count and entropion). Our SNP-based DCMS method enabled high-resolution detection of breed-specific selection signatures. It facilitated the discovery of both known and novel genomic regions, candidate genes, and QTLs unique to Indian sheep breeds. This comprehensive approach provides valuable insights into the molecular mechanisms underlying economically important traits and offers a robust foundation for targeted genetic improvement and conservation of indigenous sheep breeds.